Pengaruh Supervisi Akademik Kepala Sekolah, Iklim Organisasi, dan Kompetensi Guru terhadap Kinerja Guru Sekolah Menengah Kejuruan Negeri 1 Suak Tapeh Kabupaten Banyuasin - Utama, Ronal; Hakim, Arif Rahman; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2026)
This study seeks to examine the influence of the Principal’s Academic Supervision, Organizational Climate, and Teacher Competence, both jointly and individually, on Teacher Performance at SMK Negeri 1 Suak Tapeh, Banyuasin Regency. The research applied an associative design with a quantitative approach, employing causal relationship analysis. Data were processed using multiple linear regression with the assistance of SPSS for Windows version 22.0 at a significance level of α = 0.05.The findings reveal that principal’s academic supervision, organizational climate, and teacher competence significantly affect teacher performance. This is evidenced by an F value of 16.133, which exceeds the F table value of 2.755, with a significance level of 0.000.